2015
DOI: 10.1007/s12185-015-1802-4
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-positive diffuse large B-cell lymphoma following acute myeloid leukemia: a common clonal origin indicated by chromosomal translocation t(3;4)(p25;q21)

Abstract: Secondary non-Hodgkin lymphoma following acute myeloid leukemia (AML) is extremely rare. We here describe a unique case involving a patient who developed Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL) during complete remission (CR) of AML. A 75-year-old Japanese man was initially diagnosed with AML with maturation (FAB M2), bearing chromosomal translocation t(3,4)(p25;q21). After intensive chemotherapy, bone marrow aspiration revealed normal karyotype, and he achieved CR. Six years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There have been several reports on malignant lymphoma arising as a second malignancy in patients with hematological malignancies (3-5); however, malignant lymphoma arising from MDS following treatment with AZA is rare. EBV-positive DLBCL that is not related to HIV was almost classified among the “other iatrogenic immunodeficiency-associated lymhoproliferative disorders” or as “EBV-positive diffuse large B-cell lymphoma of the elderly” in the WHO 2008 criteria.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on malignant lymphoma arising as a second malignancy in patients with hematological malignancies (3-5); however, malignant lymphoma arising from MDS following treatment with AZA is rare. EBV-positive DLBCL that is not related to HIV was almost classified among the “other iatrogenic immunodeficiency-associated lymhoproliferative disorders” or as “EBV-positive diffuse large B-cell lymphoma of the elderly” in the WHO 2008 criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, secondary lymphoid tumors following AML are rare. Higuchi, et al reported Epstein-Barr virus-positive DLBCL during CR of AML [15]. In this case, the rearrangement patterns of the IGH in the two malignancies were different.…”
Section: Discussionmentioning
confidence: 69%
“…Diffuse large B-cell lymphoma (DLBCL) and acute myeloid leukemia (AML) rarely occur concurrently. Only a few cases of DLBCL after AML chemotherapy[ 1 , 2 ] have been reported. Chemotherapy-induced immunosuppression predisposes patients to develop secondary malignancies, particularly virus-related ones[ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few cases of DLBCL after AML chemotherapy[ 1 , 2 ] have been reported. Chemotherapy-induced immunosuppression predisposes patients to develop secondary malignancies, particularly virus-related ones[ 1 , 2 ]. Only two cases with a synchronous diagnoses of DLBCL and AML have been reported[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%